Impact of selected institutional factors on economic growth - Lim, Thong Cheen (2011)
This study examines the relationship between institutions and economic growth at various stages of economic development. The specific objectives of the study are (1) to investigate the impact of institutions on economic growth, (2) to examine the causality effect between institutions and economic growth. The dataset consists of 60 countries, which is further divided into four stages, namely low-income, lower-middle income, upper-middle income and high-income countries. The institutions dataset is obtained from International Country Risk Guide (ICRG) covering the period 1990 to 2006. The empirical results demonstrate that institutions have a significant impact on economic growth in the long-run in countries at various economic development levels except high-income countries. The results indicate that institutions (average) have positive significant impact on economic growth in lower-middle income and uppermiddle income countries. However, not all the dimensions of institutions have equal explanatory capacity. Corruption and bureaucracy quality matter for economic growth in low-income countries, whereas law and order have positive significant impact on economic growth in upper-middle income countries. Besides, the panel Granger causality results also show that there is a bi-directional causality between institutions and economic growth. Institutions are more responsive in upper-middle income countries with respect to the causal effect. Among various institutions indicators, corruption is the most important institutions indicator that has Granger causality effect with economic growth. The findings also suggest that the causality patterns between institutions and growth vary at different stages of economic development levels. As a conclusion, institutions matter for economic growth and they have different directional causality effects, but the difference is according to the different level of economic development. In terms of policy implications, this study suggests that governments or policy makers seeking to promote economic growth should focus on institutional reforms especially in lower-middle income and upper-middle income countries. Reducing corruption and improving bureaucratic quality are key factors to promote economic growth in lowincome countries, while enhancing law and order is important to achieve higher economic growth for upper-middle income countries. With respect to the causality effect, the low-income and lower-middle income countries should focus on country’s economic growth and then higher economic development will further promote better institutions. On the other hand, the uppermiddle income countries should concentrate on institutions in order to achieve greater economic growth. In addition, corruption is an important institutions indicator that must be controlled in order to enhance higher economic growth for all groups of countries.